Respostas
respondido por:
1
a) dab = √ (5-1)² + (7-1)²
dab = √ 4²+6²
dab = √ 16+36
dab = √ 52
dab = 2√13
b) dab = √(0-6)²+(6-0)²
dab = √ (-6)²+6²
dab = √36+36
dab = √72
dab = 6√2
c)dgf = √ (4-2)²+(1-3)²
dgf = √2²+(-2)²
dgf = √4+4
dgf = √8
dgf = 2√2
d) dgh = √(2-2)²+(5-1)²
dgh = √4²
dgf = 4
dab = √ 4²+6²
dab = √ 16+36
dab = √ 52
dab = 2√13
b) dab = √(0-6)²+(6-0)²
dab = √ (-6)²+6²
dab = √36+36
dab = √72
dab = 6√2
c)dgf = √ (4-2)²+(1-3)²
dgf = √2²+(-2)²
dgf = √4+4
dgf = √8
dgf = 2√2
d) dgh = √(2-2)²+(5-1)²
dgh = √4²
dgf = 4
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás